Implementasi MYOB Accounting Plus V18 dalam Pengolahan Data Akuntansi pada CV. Tiga Raya Inovasi - Ariesha Fen (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2024)
This research aims to determine the implementation of MYOB Accounting as a form of utilizing computerized accounting technology in recording and compiling financial reports for MSMEs. The research method used is descriptive qualitative with observation and interview techniques on CV. Tiga Raya Inovasi as the subject of research. The research results show that MYOB Accounting is able to produce financial reports that can be understood with a more effective and efficient work process for the company. However, several supporting factors are needed, such as awareness and ability of business actors to carry out accounting records using MYOB Accounting.